Perbedaan Keterampilan Berpikir Kritis Siswa SMAN 1 Sragen Tahun Pelajaran 2018/2019 Melalui Model Inkuiri Terbimbing Disertai Diagram Fishbone Dengan Discovery Learning - Nabela Fungky Nur Fauziah; Joko Ariyanto; Dewi Puspita Sari (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2019)
The purpose of this research was to determine the differences of student critical thinking skills in SMAN 1 Sragen in the academic year of 2018/2019 through guided inquiry model with fishbone diagram and discovery learning. This research was quasi-experimental research using quantitative approach. The research was designed using one-group posttest design. The samples of this research were established by cluster random sampling. The population of this research was all of 10th-grade students in SMAN 1 Sragen. The samples consisted of two classes, X MIPA 8 as control group using discovery learning model and X MIPA 6 as the experiment group using guided inquiry models with fishbone diagram. The data was collected by using test, observation, and documentation, and analysed by using SPSS 16. The research concluded that there is a differences of student critical thinking skills in SMAN 1 Sragen in the academic year of 2018/2019 through guided inquiry model with fishbone diagram and discovery learning.